Foucault: His Thought, His Character - Maynard, Steven (Labour / Le Travail, 2012)
The article reviews the book, "Foucault: His Thought, His Character," by Paul Veyne, translated by Janet Lloyd.
Keywords: BOOKS -- Reviews; FOUCAULT, Michel, 1926-1984; FOUCAULT: His Thought, His Character (Book); Nonfiction; VEYNE, Paul